PRACTICAL TECHNIQUES FOR TEACHING VOCABULARY TO EFL STUDENTS - marhatin, ranis; Triyogo, Agus (LP3MKIL, 2024)
This paper focuses on enhancing vocabulary learning outcomes among English as a Foreign Language (EFL) learners through practical and theoretically informed techniques. It emphasizes the crucial role of vocabulary in language acquisition, drawing from theoretical frameworks that advocate for contextual learning, interaction, and multimodal approaches. Theoretical insights highlight the necessity for engaging instructional methods tailored to diverse learner needs, supported by empirical research and pedagogical best practices. The paper categorizes effective techniques into contextual learning approaches, interactive and communicative strategies, visual and mnemonic aids, and the integration of technology in vocabulary instruction. These strategies aim to create a dynamic learning environment conducive to vocabulary acquisition in EFL classrooms. Case studies and examples demonstrate successful implementation in various educational settings, providing practical insights for educators to optimize their vocabulary teaching practices. Ultimately, the paper aims to equip educators with a comprehensive toolkit of evidence-based strategies, empowering them to facilitate vocabulary development and enhance language proficiency among EFL learners effectively.